Association between a Suppressive Combined Antiretroviral Therapy Containing Maraviroc and the Hepatitis B Virus Vaccine Response - Herrero-Fernández, Inés (Antimicrob Agents Chemother, 2017)
The response to the HBV vaccine in HIV-infected patients is deficient. Our aim was to analyze whether a suppressive combined antiretroviral treatment (cART) containing maraviroc (MVC-cART) was associated with a better response to HBV vaccine. Fifty-seven patients on suppressor cART were administered the HBV vaccine. The final response, the early response, and the maintenance of the response were assessed. An anti-HBs titer of >10 mIU/ml was considered a positive response. A subgroup of subjects was simultaneously vaccinated against hepatitis A virus (HAV). Lineal regression analyses were performed to determine demographic, clinical, and immunological factors associated with the anti-HBs titer. Vaccine response was achieved in 90% of the subjects. After 1 year, 81% maintained protective titers. Only simultaneous HAV vaccination was independently associated with the magnitude of the response in anti-HBs titers, with a P value of 0.045 and a regression coefficient (B) [95% confident interval (CI)] of 236 [5 to 468]. In subjects ≤50 years old (n = 42), MVC-cART was independently associated with the magnitude of the response (P = 0.009; B [95% CI], 297 [79 to 516]) together with previous vaccination and simultaneous HAV vaccination. High rates of HBV vaccine response can be achieved by revaccination, simultaneous HAV vaccination, and administration of cARTs including MVC. MVC may be considered for future vaccination protocols in patients on suppressive cART.